Evaluation of developmental competence of Sus scrofa domesticus (L.) oocyte-cumulus complexes after intra- and extraovarian vitrification - T. I. Kuzmina; I. V. Chistyakova (Вавиловский журнал генетики и селекции)
The aim of the present study was to identify the influence of extra- (EOV) and intraovarian vitrification (IOV) on mitochondrial activity (MA) and chromatin state in porcine oocytes during maturation in vitro. During EOV porcine oocytes were exposed in cryoprotective solutions (CPS): CPS-1 – 0.7 M dimethyl sulfoxide (DMSO)+0.9 M ethylene glycol (EG); CPS-2 – 1.4 M DMSO+1.8 M EG; CPS-3 – 2.8 M DMSO+3.6 M EG+0.65 M trehalose. At IOV the ovarian fragments were exposed in CPS-1 – 7.5 % EG+7.5 % DMSO, then in CPS-2 – 15 % EG, 15 % DMSO and 0.5 M sucrose. Straws with oocytes and ovarian fragments were plunged into LN2 and stored. For devitrification, the EOV oocytes were washed in solutions of 0.25, 0.19 and 0.125 M of trehalose, the IOV – in 0.5 and 0.25 М trehalose. Oocytes were cultured in NCSU-23 medium with 10 % fluid of follicles, follicular walls, hormones. 0.001 % of highly dispersed silica nanoparticles (ICP named after A.A. Chuyko of the NAS of Ukraine) were added to all media. The methods of fertilization and embryo culture are presented in the guidelines developed by us. MA and chromatin state were measured by MitoTracker Orange CMTMRos and the cytogenetic method. Significant differences in the level of oocytes with high-expanded cumulus between control and experimental vitrified groups (81 % versus 59 % and 52 %, respectively, p ≤ 0.001) were observed. The percentage of pyknotic cells in native oocytes was 19 %, EOV or IOV oocytes were 39 % and 49 %, respectively. After culture, the level of matured native oocytes was 86 %, 48 % EOV and 33 % IOV cells finished the maturation (p ≤ 0.001). Differences were also observed in the level of MA between groups treated by EOV and IOV (89.4±7.5 µA and 149.2±11.3 µA, respectively, p ≤ 0.05). For the first time, pre-implantation embryos were obtained from oocytes treated by IOV.